The unintended effects of the Common Core State Standards on non-targeted subjects - Benjamin W. Arold; M. Danish Shakeel (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
From 2010 onwards, most US states have aligned their education standards by adopting the Common Core State Standards (CCSS) for math and English Language Arts. The CCSS did not target other subjects such as science and social studies. We estimate spillovers of the CCSS on student achievement in non-targeted subjects in models with state and year fixed effects. Using student achievement data from the NAEP, we show that the CCSS had a negative effect on student achievement in non-targeted subjects. This negative effect is largest for underprivileged students, exacerbating racial and socioeconomic student achievement gaps. Using teacher surveys, we show that the CCSS caused a reduction in instructional focus on nontargeted subjects.
Keywords: H75; I21; I24; I28; J24; 330; Common core; education standards; student achievement; education policy